Assessing the effectiveness of clove, star anise, and curry leaves as natural repellents against dipteran insects - Mohd Arwansyah, Nurul Natasya Nabilla; Noor Azman, Nur Nadhirah Syafiqah; Hasmi, Nur Atirah (2024)
The use of commercialized fly repellent containing DEET (N, N-diethyl-meta-toluamide) which is present in many repellent formulations can affect humans’ health and the air quality. The significance of this research is to provide natural repellent, which is affordable, easy-access and less toxic to human health. Furthermore, curry leaves, cloves, and star anise are edible herbs that are nontoxic, safe for kids, and they do not contain any chemicals that could be damaging to skin. The objective of this project is to examine the effectiveness of these three natural spices and herbs (Illicium verum, Murraya koenigii and Syzygium aromaticum), and thus to provide the repellents that are environment friendly. The extractions of curry leaves, cloves, and star anise were used in this study. The extraction of clove is the most effective in repelling the Diptera rather than curry leaves and star anise because of special components called eugenol and carbazole alkaloids that have antioxidant, and insecticidal properties that are used against flies. The suitability also considers aspects like safety, convenience of preparation, and any negative reactions or side effects. It can be concluded that the natural plant resources can be used in reducing the number of flies and repel Diptera in a way that are affordable, less toxicity, environment friendly, and providing a safer and greener alternative to chemical repellents. The findings will be useful in determining the best natural repellent technique for everyday use.